Does A Wealth Tax Improve Equality of Opportunity? - Kristoffer Berg; Shafik Hebous (Center for Economic Studies and ifo Institute (CESifo), 2021)
Does parental wealth inequality impact next generation labor income inequality? And does a tax on parental wealth affect the labor income distribution of the next generation? We tackle both questions empirically using detailed intergenerational data from Norway, focusing on effects on wages rather than capital income. Results suggest that a net wealth of NOK 1 million increases wages of the children by NOK 14,000. Children of wealthy parents also have a higher labor income mobility. The estimated hypothetical wage distribution without the wealth tax is more unequal. Moreover, suggestive evidence indicates parental wealth is associated with higher labor risk taking.
Keywords: D31; D63; H24; 330; wealth tax; equality of opportunity; parental wealth; income mobility; inequality; redistribution